Peran Notaris dalam Perlindungan Hukum Hak Atas Tanah Masyarakat Lokal dalam Pembangunan IKN Berdasarkan UU No. 3 Tahun 2022 - Ilyas Budi Saputra (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
The relocation of the National Capital (IKN) through Law Number 3 of 2022 raises the potential for serious issues related to the land rights of local communities, particularly indigenous communities who have long inhabited and utilized the area. In the context of IKN development, community rights often clash with the interests of the state and investors, thus creating the risk of violations of basic rights, including land rights, which are an important part of their social, cultural, and economic identity. Notaries, as public officials, have a strategic role in ensuring that every process of transferring land rights is carried out legally, fairly, and in accordance with legal provisions. This study aims to analyze the extent to which the IKN Law protects the rights of local communities and how the role of notaries in notarial practice can ensure justice for the parties involved. The research method used is normative juridical with a qualitative approach through a review of regulations, legal doctrine, and an analysis of notarial practices relevant to IKN development. The results show that although the IKN Law contains general norms regarding respect for the rights of local communities, the legal protection provided is still weak and has not been accompanied by adequate technical regulations. The role of notaries in this context has also been suboptimal due to limited scope of authority and the lack of specific guidelines for overseeing the transfer of land rights in the new capital development area. This research emphasizes the need to strengthen derivative regulations and optimize the role of notaries to serve as a crucial instrument in ensuring legal certainty, justice, and the protection of the rights of indigenous communities during the new capital development.